(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2015)
Prolonged high fever is a common clinical problem and sometimes the diagnosis is difficult, management can be a challenge to the clinicians. Adult onset Stills Disease is a rare systemic inflammatory disorder of unknown etiology that is responsible for a significant proportion of cases of fever of unknown origin and can also have serious musculoskeletal sequelae. The disease presents as a diagnostic and therapeutic challenge to the clinicians and clinical guidelines are lacking. The emergence of classification criteria, discovery of better serological markers and the application of new biological agents may all provide the clinicians with significant tools for the diagnosis and management of this complex disorder J Bangladesh Coll Phys Surg 2014; 32: 224-228